Hukum Konstitusi di Indonesia Perspektif Mahfud MD - Dinar Rosyiddin Alifian Romadhon (CV Edujavare Publishing, 2024)
The purpose of writing this work is to understand constitutional law in Indonesia from Mahfud MD's perspective. This research adopts a qualitative approach to deepen understanding of constitutional law in Indonesia from Mahfud MD's perspective. The literature review involves studying literature related to constitutional law theory and the work of Mahfud MD as the main reading material. The main data source comes from Mahfud MD's writings, including books, articles and speeches discussing constitutional law in Indonesia. Data collection techniques include literature study, document analysis, and a review of Mahfud MD's online publications. Data analysis was carried out using a qualitative descriptive approach, identifying the main concepts and views of Mahfud MD through comparison and synthesis of information. Legal politics in the Indonesian context, both before and after the amendments to the 1945 Constitution, provides a historical perspective on the evolution of the Indonesian legal framework and its impact on the direction of law formation. Mahfud MD's understanding that legal politics is an official and valid legal policy, which determines the direction, form and substance of laws, provides a basis for seeing the complex relationship between politics and law.